2017
DOI: 10.1016/j.jneb.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Using Skin Carotenoids to Assess Dietary Changes in Students After 1 Academic Year of Participating in the Shaping Healthy Choices Program

Abstract: The reported decrease in vegetable and carotenoid intake was unanticipated; nevertheless, the RRS measurements confirmed this. RRS data can help evaluate changes in fruit and vegetable intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Furthermore, the Veggie Meter® is objective and overcomes bias inherent in self‐reported FV intake measures ( 6,7 ) . Although previous studies have been conducted using the RRS in school‐ based settings ( 11,12 ) , the present study is the first to report on use of the Veggie Meter® in three diverse preschool and school‐based populations. More studies are needed with children and adolescents in order to assess the validity (comparing with plasma‐assessed carotenoids) and reproducibility of the Veggie Meter® in these populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the Veggie Meter® is objective and overcomes bias inherent in self‐reported FV intake measures ( 6,7 ) . Although previous studies have been conducted using the RRS in school‐ based settings ( 11,12 ) , the present study is the first to report on use of the Veggie Meter® in three diverse preschool and school‐based populations. More studies are needed with children and adolescents in order to assess the validity (comparing with plasma‐assessed carotenoids) and reproducibility of the Veggie Meter® in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, HPLC analysis of blood carotenoids is expensive, invasive and impractical, particularly in school‐based settings. Skin carotenoid status assessed by resonance Raman spectroscopy (RRS) is a valid biomarker of FV intake ( 10 ) and has been used in school‐based interventions ( 11,12 ) . However, RRS has limitations as a result of the lack of portability of the hand‐built RRS machines, and the RRS devices that are portable are only available to researchers through a lease agreement, where researchers pay a specific amount of money to use the RRS device for a specific amount of time, after which they must return the device to the company that owns the patent to the RRS device (Pharmanex, Provo, UT, USA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research supports youth under age 10 years have difficulty with specific recall, which may explain why many youths did not remember specific messages from the 26 total messages received over the course of 9 months. 25,26…”
Section: Discussionmentioning
confidence: 99%
“…When measuring consumption is impractical, self-report measures should be supplement by biomarkers of FV consumption. In evaluating the effects of an education-based intervention (Beccarelli et al, 2016), self-reported FV consumption was unchanged at the conclusion of the 9-month intervention. However, skin carotenoid levels (a biomarker of FV consumption) significantly declined at the intervention's end, suggesting not only that the education-based program was ineffective but also that self-report assessments were either insensitive or invalid.…”
Section: Education and Messagingmentioning
confidence: 99%